Comparative Analysis of Smart Meters Deployment Business Models on the Example of the Russian Federation Markets; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Daminov I. B. Ildar Bolatovich; Tarasova E. S. Ekaterina Sergeevna; Andreeva T. Tatyana; Avazov A. Artur (2016, 2016)
Title screen